Genome Wide Analysis of Single Nucleotide Polymorphism of Human Mitochondrial Genome in Indian Population - Saxena, Vijaylaxmi; Dixit, Supriya; Shukla, Krati (Asian Journal of Biological and Life Sciences, 2015)
The human mitochondrial genome is extremely small compared with the nuclear genome and also have high rate of mutations which will lead to a disease like cancer, ageing and neurodegenerative disease. A major challenge for linkage disequilibrium in mitochondrial genome studies is the high cost of genotyping large number of single nucleotide polymorphisms and to predict correlations between them to find out informative SNP which is able to cause variations among population. The main aim of this research to find out an efficient method for finding SNPs, and linkage within, thus analyzing polymorphism in human mitochondrial genome in Indian population. A total of 1284 SNPs were identified in the dataset of mitochondrial genome of Indian population and LD analysis was done to know the potential SNP which will be the cause of disease in the particular population but no significance results were found. This set of SNP markers found in dataset represents a useful tool for genetic studies in mitochondrial genome and will be useful in identifying candidate genes that affect diverse ranges of phenotypes
Keywords: linkage disequilibrium; Mitochondrial genome; Mutations; single nucleotide polymorphisms